STAT3, tumor microenvironment, and microvessel density in diffuse large B cell lymphomas. Issue 3 (23rd February 2020) - Tamma, Roberto; Ingravallo, Giuseppe; Gaudio, Francesco; Annese, Tiziana; Albano, Francesco; Ruggieri, Simona; Dicataldo, Michele; Maiorano, Eugenio; Specchia, Giorgina; Ribatti, Domenico
Abstract: Constitutively activated STAT3 is correlated with more advanced clinical stage and overall poor survival of diffuse large B-cell lymphoma (DLBCL). The aim of this study was to evaluate STAT3 and Ki67 tumor cell expression, inflammatory cell infiltration, microvascular density in DLBCL bioptic specimens. RNA-scope showed that activated B cell (ABC) tissue samples contained a significant higher number of STAT3+ cells as compared to germinal center B (GCB) tissue samples. Immunohistochemical analysis showed a significant increased levels of CD3, CD8, CD68, CD163, CD34, and Ki67 positive cells in ABC patients. A positive correlation between STAT3 and CD3, CD8, CD68, and CD163 was evidenced in ABC group. In ABC group, we found also a positive correlation between CD8 and CD34 and a positive correlation between Ki67 and, CD68, and CD163. These data indicate that in ABC—as compared to GCB-DLBCL, a higher STAT3 expression is associated with a higher CD163+ TAM and CD8+ cell infiltration which induces a strong angiogenic response.